2023
DOI: 10.26434/chemrxiv-2023-7cl1d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Guanine quantum defects in carbon nanotubes for biosensing

Abstract: Fluorescent single wall carbon nanotubes (SWCNTs) are used as nanoscale biosensors in diverse applications. Selectivity is built in by non-covalent functionalization with polymers such as DNA. In general, fluorescence sensing with SWCNTs would benefit from covalent DNA-conjugation but it is not known how changes in conformational flexibility and photophysics affect the sensing mechanism. Recently, covalent functionalization was demonstrated by conjugating guanine bases of adsorbed DNA to the SWCNT surface as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. 38,39 Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. 40,41 It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects.…”
mentioning
confidence: 99%
“…This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. 38,39 Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. 40,41 It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects.…”
mentioning
confidence: 99%
“…126−129 Galonska and Kruss et al demonstrated enhanced sensitivity in detecting dopamine by using (GT) 10 -ssDNA-coated (6,5)-SWCNTs, specifically through covalent bonding that introduced guanine quantum defects. 130 Covalent sp 3 defects on carbon nanotubes (also called organic color centers) (6,5)-(GT) 15 were used in monitoring autophagy-associated lysosomal acidification in vivo and were designed to detect pH changes in the lysosomal environment of living cells and in vivo models. 131 The utilization of time-correlated single-photon counting techniques has provided insights into the photoluminescence lifetime of the E 11 * defect emission, demonstrating a notable extension compared to the lifetime of mobile excitons.…”
Section: Chirality-sorted/monochiral Swcntsmentioning
confidence: 99%
“…47 As defect density depends on the RB concentration and the guanine content, one can pattern and tailor SWCNT surfaces. 40−42,47−49 Apart from the mechanistic and photophysical studies concerning this reaction, [40][41][42]47,48 as well as the signal observed upon the adsorption of small molecules, 49 this chemistry has up to our knowledge not been used for rational sensing.…”
Section: ■ Introductionmentioning
confidence: 99%